The dilemma of internal auditor independence in multinational companies: A phenomenological study - Kadar, Muhammad Gafur; Amiruddin, Amiruddin; Darmawati, Darmawati; Syarifuddin, Syarifuddin (Edelweiss Applied Science and Technology, 2026)
This study aims to gain an in-depth understanding of how the dilemma of internal auditor independence is constructed, experienced, and negotiated within the social context of multinational companies. Using Anthony Giddens’ structuration theory, it views independence not merely as a normative principle of the auditing profession but as a reflective social action that is continuously produced and reproduced through interactions among auditors, management, and organizational structures. To explore the experiences of internal auditors facing independence dilemmas, the study adopts a phenomenological approach. The informants include internal auditors as the main participants and financial or operational managers as additional informants. The findings show that the independence of internal auditors is dynamic and contextual. Based on Giddens’ three dimensions of structuration: 1. Signification, auditors construct the meaning of independence through professional language and ethical communication strategies. 2. Domination, auditors navigate power relations with management through negotiation rather than confrontation. 3. Legitimacy, auditors maintain moral authority by updating procedures, maintaining integrity, and upholding professional values.